2005
DOI: 10.1536/ihj.46.761
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Response to Oral Glucose Loading and Coronary Artery Disease in Nondiabetics

Abstract: SUMMARYHyperinsulinemia is related to coronary artery disease (CAD), as an indication of decreased insulin sensitivity. Although there are many studies showing the relation between fasting insulin levels and insulin resistance, there are fewer studies on postprandial insulin levels. The aim of the present study was to investigate the relationship between postprandial insulin levels and CAD and its extent in our patients. For this purpose, oral glucose tolerance testing was performed in 222 patients with no kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…R.A. DeFronzo et al demonstrated for the first time that individuals with angiographically documented CAD are characterized by insulin resistance 16) . It is well known that insulin resistance is directly related to the occurrence of atherosclerosis and the risk for cardiovascular diseases [17][18][19] ; however, few studies have focused on the relationship between insulin secretion and coronary atherosclerosis 3,4,20) . Moreover, these studies did not investigate beta cell function together with insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R.A. DeFronzo et al demonstrated for the first time that individuals with angiographically documented CAD are characterized by insulin resistance 16) . It is well known that insulin resistance is directly related to the occurrence of atherosclerosis and the risk for cardiovascular diseases [17][18][19] ; however, few studies have focused on the relationship between insulin secretion and coronary atherosclerosis 3,4,20) . Moreover, these studies did not investigate beta cell function together with insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the research has been concerned with the correlation between hyperinsulinemia and/or insulin resistance and atherosclerosis and/or cardiovascular events. It is well known that insulin resistance and hyperinsulinemia are major candidates contributing to the development of atherosclerosis in patients; however, few studies have focused on the role of insulin secretion during the development of atherosclerosis 3,4) . Beta cell dysfunction and/or insulin resistance are two important pathophysiological factors in type 2 diabe-one year).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although the current incidence of atherosclerotic diseases in Japan is relatively low compared to that in other countries, an increase is expected in the near future with the increase of diabetic patients. Therefore, treatment for atherosclerosis in diabetic patients is an important concern.…”
mentioning
confidence: 99%
“…For analyses of between-meal differences, the 2 h time point was chosen because published studies looking at postprandial hyperinsulinemia 5,7,8,13 have used this time point, at which glucose and insulin levels are expected to have returned to normal values in healthy subjects. Plasma glucose concentrations normally peak within 1 h after a meal and return to normal values within 2-3 h. 14 Population studies of postprandial hypertriglyceridemia have found it to be most predictive of cardiovascular events when measured 2 to 4 h after eating.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 In subjects with no known diabetes, high postprandial insulin levels have been found to be an independent risk factor for CHD. 7,8 Triglyceride levels measured 2-4 h after a meal are also highly predictive of cardiovascular events, especially in women. 9,10 Cardiometabolic risk markers are routinely measured in fasting blood samples in order to provide meaningful levels of cholesterol, insulin, and triglycerides that are not affected by recent food consumption.…”
Section: Introductionmentioning
confidence: 99%